Assessing the Role of Health Behaviors, Socioeconomic Status, and Cumulative Stress for Racial/Ethnic Disparities in Obesity. Issue 1 (20th December 2019) - Cuevas, Adolfo G.; Chen, Ruijia; Slopen, Natalie; Thurber, Katherine A.; Wilson, Norbert; Economos, Christina; Williams, David R.
Abstract : Objective: This study aimed to examine the explanatory role of health behaviors, socioeconomic position (SEP), and psychosocial stressors on racial/ethnic obesity disparities in a multiethnic and multiracial sample of adults. Methods: Using data from the Chicago Community Adult Health Study (2001‐2003), Oaxaca‐Blinder decomposition analysis was conducted to quantify the extent to which health behaviors (fruit and vegetable consumption and physical activity), SEP, and cumulative stressors (e.g., perceived discrimination, financial strain) each explained differences in obesity prevalence in Black, US‐born Hispanic, and non‐US‐born Hispanic compared with non‐Hispanic White participants. Results: SEP and health behaviors did not explain obesity differences between racial/ethnic minorities and White individuals. Having high levels of stress in four or more domains explained 4.46% of the differences between Black and White individuals, whereas having high levels of stress in three domains significantly explained 14.13% of differences between US‐born Hispanic and White. Together, the predictors explained less than 20% of differences between any racial/ethnic minority group and White individuals. Conclusions: Exposure to stressors may play a role in obesity disparities, particularly among Black and US‐born Hispanic individuals. Other obesity‐related risk factors need to be examined to understand the underlying mechanisms explaining obesity disparities.